2021
DOI: 10.1016/j.fusengdes.2021.112661
|View full text |Cite
|
Sign up to set email alerts
|

Structural integrity of DEMO divertor target assessed by neutron tomography

Abstract: The divertor target plates are the most exposed in-vessel components to high heat flux loads in a fusion reactor due to a combination of plasma bombardment, radiation and nuclear heating. Reliable exhaust systems of such a huge thermal power required a robust and durable divertor target with a sufficiently large heat removal capability and lifetime. In this context, it is pivotal to develop non-destructive evaluation methods to assess the structural integrity of this component that, if compromised could reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A detailed description of the mock-up manufacturing process is report in this work [8] and it has been listed in the reference for interested readers. This sample was previously studied via neutron tomography [4] on the IMAT beamline [9][10][11][12][13][14][15] at the ISIS spallation neutron source in the UK. Further, recent studies have demonstrated the feasibility of using neutron tomography to assess volumetric defects on large numbers of similar components like divertor monoblocks [13] and how those results compared with XCT measurements [16].…”
Section: Demo Divertor Mock-up Sample and Previous Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of the mock-up manufacturing process is report in this work [8] and it has been listed in the reference for interested readers. This sample was previously studied via neutron tomography [4] on the IMAT beamline [9][10][11][12][13][14][15] at the ISIS spallation neutron source in the UK. Further, recent studies have demonstrated the feasibility of using neutron tomography to assess volumetric defects on large numbers of similar components like divertor monoblocks [13] and how those results compared with XCT measurements [16].…”
Section: Demo Divertor Mock-up Sample and Previous Testingmentioning
confidence: 99%
“…Further, recent studies have demonstrated the feasibility of using neutron tomography to assess volumetric defects on large numbers of similar components like divertor monoblocks [13] and how those results compared with XCT measurements [16]. From the neutron tomography tests [4], no major issues have been identified within the sample. Subsequently, the specimen was subjected to HHF loads with a single cycle at ∼8 MWm −2 on the HIVE facility [17] at United Kingdom Atomic Energy Authority (UKAEA).…”
Section: Demo Divertor Mock-up Sample and Previous Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutron imaging is one of the most promising techniques to study in situ and operando processes of interest for industrial and engineering applications [1][2][3][4][5][6][7][8][9][10][11] as well as for cultural heritage. [12][13][14][15][16][17][18][19] The technique exploits the high penetration power of neutrons, along with a number of features in the way they interact with nuclei and isotopes, and the fact that neutrons are available in dedicated research infrastructures in a broad range of energies spanning several orders of magnitude, from tens of meV to hundreds of MeV.…”
Section: Introductionmentioning
confidence: 99%